PERILAKU SUKSES PETANI MUDA WIRAUSAHA LULUSAN FAKULTAS PERTANIAN UNIVERSITAS PADJADJARAN - Gema Wibawa Mukti; Rani Andriani Budi Kusumo; Sara Ratna Qanti (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2017)
Entrepreneurship becomes an important thing for the development. Developed countries have a large number of entrepreneurs that can become the pillar in the development. Entrepreneurial culture certainly gives influence to the success of a businessman. This study aimed to analyze entrepreneurial behavior of young farmers who are considered successful. This sudy showed that young farmers who graduated from the Faculty of Agriculture consider that successful farmers were farmers who are able to apply their knowledge and experience in agriculture to the real world. Successful farmers were those who are constantly on the lookout for markets and always learning new things every day, they feel a loss if in one day they find nothing new to learn. Successful farmers were those who have successful behaviors such as will to find a solution and work hard to get that, it is a strong capital for young farmers to survive and grow in their business. Success in agriculture should be obtained by working diligently (istiqomah), always understanding the needs and wants of the market, always strengthening the knowledge of business management, having a consistent entrepreneurial spirit, always keeping up with the information technology and being able to adapt to the dynamic environment.